Global and regional estimates of vaccine-associated herpes zoster and their related vaccines from 1969 to 2023 - Jinyoung Jeong; Hyesu Jo; Yejun Son; Jaeyu Park; Jiyeon Oh; Sooji Lee; Yi Deun Jeong; Kyeongmin Lee; Hyeon Jin Kim; Hayeon Lee; Soeun Kim; Yesol Yim; et al. (Scientific Reports)
Abstract Vaccine-induced immunosuppression can reactivate the varicella-zoster virus, potentially leading to the development of herpes zoster. However, the literature on this topic is inconsistent, resulting in limited clarity. Therefore, we aimed to enhance our understanding of vaccine-associated herpes zoster and establish guidelines for future research, utilizing a global database to improve global public health. We investigated vaccine-associated adverse events in herpes zoster using reports (~ 13 million reports) from the WHO international pharmacovigilance database. Data were analyzed for the global number of reports, reported odds ratios (ROR), and information components (IC) to determine the potential association between 18 vaccines and vaccine-associated herpes zoster reports in nearly 170 countries and territories from 1969 to 2023. Of 7,805,380 vaccine-associated adverse events, there were 51,985 herpes zoster reports. Vaccine-associated herpes zoster showed the highest strength of association with COVID-19 mRNA vaccines (ROR, 11.85 [95% CI, 11.70-12.01]; IC, 2.74 [IC0.25, 2.72]), followed by encephalitis (ROR, 4.07 [95% CI, 3.37–4.92]; IC, 2.00 [IC0.25, 1.68]), influenza (ROR, 3.44 [95% CI, 3.28–3.62]; IC, 1.77 [IC0.25, 1.69]), and ad5-vectored COVID-19 vaccines (ROR, 3.05 [95% CI, 2.97–3.14]; IC, 1.54 [IC0.25, 1.50]). The ROR and IC of vaccine-associated herpes zoster in males (ROR, 7.94 [95% CI, 7.80–8.08]; IC, 2.47 [IC0.25, 2.45]) and females (ROR, 6.71 [95% CI, 6.62–6.80]; IC, 2.30 [IC0.25, 2.28]). The ROR and IC increased with advancing age. Our findings emphasize the need to consider the immune status of vaccine recipients and to implement appropriate compensation and management manuals for vaccine-associated herpes zoster.